Copper oxide nanoparticles recruit macrophages and modulate nitric oxide, proinflammatory cytokines and PGE2 production through arginase activation. (May 2016) - Arancibia, Sergio; Barrientos, Andrea; Torrejón, Javiera; Escobar, Alejandro; Beltrán, Caroll J
Aim : In the present study, we examine the effects of copper oxide nanoparticles (CuNP) on macrophage immune response and the signaling pathways involved.Materials & Methods: A peritonitis model was used to determine in vivo immune cells recruitment, while primary macrophages were used as an in vitro model for the cellular and molecular analysis.Results:   In vivo, CuNP induce significant macrophages recruitment to the site of injection. In vitro, in LPS-stimulated primary macrophages, the co-treatment with CuNP inhibited the production of NO in a dose-dependent manner. The mechanism underlying NO and proinflammatory cytokines inhibition was associated with an increased arginase activity. Macrophage stimulation with CuNP did not provoke any cytokine secretion; however, arginase inhibition promoted TNFα and MIP-1β production. In addition, CuNP induced the expression of COX-2 and the production of PGE2 through arginase activation.Conclusion: Our results demonstrate that CuNP activate arginase and suppress macrophage innate immune response.